Variation and reason analysis of groundwater hydrochemical characteristics in Beiluhe Basin, Qinghai–Tibet Plateau during a freezing–thawing period. Issue 7 (8th July 2022) - Liu, Zejun; Fang, Yahong; Hu, Haiyang; Wang, Wei
Abstract: Groundwater in the Qinghai–Tibet Plateau (QTP) is mainly distributed in the active layer. Rising temperatures and human activities have influenced the hydrogeochemical characteristics of the QTP in recent years. This study investigates the hydrochemistry and stable isotope ( δ 18 O and δ D) variations of the groundwater in the Beiluhe Basin, which is located in the QTP of China, during a freezing–thawing period of the active layer. Results show the chemical types of the groundwater are mainly HCO3 Cl–Na Ca Mg, which are converted to Cl HCO3 –Na Ca Mg during the freezing period of the active layer. At different stages of the freezing–thawing period of the active layer, evaporation, concentration, and rock weathering control the chemical composition of the groundwater in this region. The main ion ratio coefficients of groundwater and the saturation indices of related minerals in groundwater indicate that halite, dolomite, and calcite control the relevant chemical components of water in the study area. The stable isotopic results show that δ 18 O and δ D fluctuations in the lake water and the groundwater are mainly affected by groundwater runoff, temperature, and evaporation. This study provides the scientific basis for groundwater evolution and utilization in high-altitude areas. HIGHLIGHTS: The hydrogeochemical variation of groundwater in active layer located in cold regions during a freezing–thawing period is studied. A rigorous analysis of the variation reason using the Piper diagram, Gibbs diagram, the main ion proportionality coefficients, and the main mineral saturation index is performed. Not only the conventional ion but also the isotope ions are analysed. Reverse hydrogeochemical simulations are used to support the results. Graphical Abstract